(untitled) (Scientific Journal of Informatics, 2024)
Purpose: This research scrutinizes the impact of NEW SAKPOLE on increasing Original Local Government Revenue (PAD) post-pandemic in Central Java Province BAPENDA. Methods: This research employed qualitative methods with a descriptive research approach. The types and sources of data used were primary and secondary data. Data collection techniques were conducted by looking for references from various sources, such as reports, previous research journal articles, and news sources related to research. Since the data analysis techniques utilized in NEW SAKPOLE application research must be appropriate to the data collection type, qualitative analysis was performed to analyze data collected from interviews, observations, and FGDs. Result: The research results uncovered that NEW SAKPOLE is a public service innovation by the Central Java Government that encourages people to be obedient and disciplined when paying motor vehicle taxes. Implementing this application service is highly effective, as it can save people’s time and energy and does not cause crowds, especially during and after the pandemic. Other governments can imitate this innovation to increase revenue from the tax sector, especially the motor vehicle tax sector, which potentially increases Original Local Government Revenue in Central Java Province. Novelty: This research enriches literature by discovering the impact of implementing NEW SAKPOLE on increasing Original Local Government Revenue. This research provides new insights and sound examples for related parties regarding implementing the E-SAMSAT application in facilitating Motor Vehicle Tax (PKB) payments by considering post-COVID-19 as the current condition when this research was conducted. This study also completes a sector-by-sector analysis that has yet to be carried out in previous studies regarding the implementation of NEW SAKPOLE.